2013
DOI: 10.4314/ahs.v12i4.16
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic effect of kolaviron, a biflavonoid complex isolated from Garcinia kola seeds, in Wistar rats

Abstract: Background: Hypoglycaemic effect of kolaviron (KV), (biflavonoid from Garcinia kola) in streptozotocin (STZ)-diabetic rats has been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 29 publications
(24 reference statements)
1
32
0
1
Order By: Relevance
“…Biflavonoids are flavonoid dimers that have been attached to each other by either C-C or C-O-C bonds representing a variety of chemical structures [2]. Several biological activities such as antioxidant [3,4], antiviral [5], hypolipidemic [6], antidiabetic [7], anti-tumoral [8], antituberculosis [9], antimalarial [10], antibacterial [11], antifungal [12], and anti-inflammatory [13] effects have been reported for biflavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…Biflavonoids are flavonoid dimers that have been attached to each other by either C-C or C-O-C bonds representing a variety of chemical structures [2]. Several biological activities such as antioxidant [3,4], antiviral [5], hypolipidemic [6], antidiabetic [7], anti-tumoral [8], antituberculosis [9], antimalarial [10], antibacterial [11], antifungal [12], and anti-inflammatory [13] effects have been reported for biflavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…During diabetes, the activities of the aminotransferases are elevated. 44 The administration of ISTPPLG NPs produced a significant decrease in serum ALT activity, which was comparable to that of normal control.…”
Section: Effect Of Istpplg Nps On Lipid Profiles and Status Of Biochementioning
confidence: 66%
“…Serum and cardiac protein, CK-MB and LDH levels were assayed by the methods described by Adaramoye [12].…”
Section: Protein Creatine Kinase Mb (Ck-mb) and Lactate Dehydrogenasmentioning
confidence: 99%
“…Extracts of the plant have been used in African herbal medicine for the treatment of laryngitis, heart burns, liver diseases, cough and hoarseness of voice [10]. Kolaviron (KV) is a bioflavonoid complex isolated from the seeds of G. kola and has been reported to possess anti-inflammatory, antidiabetic, antioxidant, antigenotoxic and hepatoprotective activities in model systems via multiple biochemical mechanisms [11,12]. Early studies by Adaramoye et al [13] and Adaramoye and Medeiros [14] showed the anti-atherogenic and vasorelaxant effects of KV in an animal model and isolated smooth muscle, respectively.…”
Section: Introductionmentioning
confidence: 99%